AB0739 Assessment of Skin Involvement in Patients with Polyarticular Psoriatic Arthritis after 30 Months of Biological Therapy Optimization. (15th July 2016) - Rodriguez Valls, M.J.; Marquez Enriquez, J.; Aranda-Valera, C.; Cabello Fernandez, Y.; Toledo Coello, M.D.; Perez Venegas, J.J.
Abstract : Background: Some patients with psoriatic arthritis (PA) in optimizing biological therapy present joint and/or skin activity, and they need to return to the standard dose of the drug. We present the articular and skin Activity Data in our cohort of patients with polyarticular psoriatic arthritis (PPA) in therapeutic optimization Objectives: Assessment of the cutaneous activity by the PASI (Psoriasis Area Severity Index) and NAPSI (Nails Psoriasis Severity Index) scales and the analysis of the joint clinical course by DAS28 in PPA patients with biological treatment followed in the Rheumatology section of an university hospital of Jerez (Cadiz, Spain), which are undergoing therapeutic optimization. Methods: An observational, descriptive, longitudinal and retrospective study by reviewing medical records, between January 2013 and January 2016, of PPA patients carrying at least 6 months in remission (DAS28 <2.6) or minimal activity (DAS28 2.6–3.2) and those who underwent optimization of biological therapy. Demographics, duration of PPA before the use of biological, biological time optimization, clinical evaluation by DAS28 pre and post-optimization, therapeutic strategy and assessment of skin activity by the PASI and NAPSI scales. Statistical analysis with the SPSS Statistics 22.0 software version is performed. Results: From a total of 120 patients with PA in biological treatment, 26 of them with only polyarticular involvement (20.83%) were performed optimization of the therapy. 61.5% are male. Mean age 50±13 years. Average time optimized treatment dose: 31±14 months. 11 patients (42%) performed adalimumab 40 mg/15 days optimizing his administration every 21 days; 15 (57%) patients initially performed etanercept 50 mg/7 days were optimized to 25 mg/7 days (9 patients (34%)), 50 mg/10 days (2 (7%)) or 50 mg/15 days (4 (15%)). At the time of optimization, 25 (96.2%) patients presented remission DAS28 and 1 (3.8%) low activity, continuing in the same situation at the time of the end of the study (30 months after optimization). However, 5 patients (19.2%) (4 from etanercept group and 1 from adalimumab group) required to return to full doses of biologic drug for clinical worsening, agreeing worsening skin, remaining stable clinical joint. The skin evaluation was average PASI 1.95±2.13 (0–72) and medium NAPSI 11.19±11.38 (0–160), presenting patients who required back to initial biological dose PASI values between 1.6 and 5.8 and NAPSI values between 20 and 32, with prevalence of nail disease in the lower limbs. One patient (3.8%) required changing biological undesirable effects (anal fistula) Conclusions: 77% of patients with PPA in remission or low activity subject to therapeutic optimization in our center remained stable at an average of 31 months of optimization, allowing continued the biological treatment in optimized doses. The main cause of return to full doses of biologic therapy in the remaining 33% of cases was worsening cutaneous involvement, remaining stable clinical joint in 100% of patients of our study Disclosure of Interest: None declared